Risk factors for the presentation of supraventricular arrhythmias in patients residing at high altitudes - Beraún-Barrantes, José (2026)
Objective. To determine the risk factors associated with the occurrence of supraventricular arrhythmias (SVA) among residents at high altitude. Material and methods. We conducted an analytical observational casecontrol study, including 24-hour electrocardiographic monitoring and transthoracic echocardiography in 192 individuals. Logistic regression analysis was used for statistical evaluation. Results. The study included 96 cases and 96 controls. Mean age was higher among cases than controls (65.9 ± 13.6 vs. 47.5 ± 19.5 years; p<0.001). Progressive increases in age, systolic blood pressure, and pulse pressure were significantly associated with a higher incidence of SVA. In multivariable analysis, hypertension (Odds Ratio [OR] = 3.43, 95% confidence interval [CI]: 1.64-7.16; p<0.001) and pulse pressure greater than 50 mmHg (OR = 3.27, 95% CI: 1.61-6.65; p=0.001) were independently associated with the presence of SVA. Hypertensive patients had more than a threefold increased likelihood of developing SVA compared with normotensive individuals. Episodes of supraventricular tachycardia were significantly more frequent among hypertensive participants than among non-hypertensive participants (60.6% vs. 39.4%; p<0.001). Conclusion: Hypertension and elevated pulse pressure are significant risk factors for the development of SVA among residents at high altitude. Further studies are warranted to clarify the clinical implications for prevention and management of SVA in hypertensive patients.